Drug-Resistant Tuberculosis Among Children: A Systematic Review and Meta-Analysis - Song, Wan-mei; Li, Yi-fan; Liu, Yun-xia; Liu, Yao; Yu, Chun-bao; Liu, Jin-yue; Li, Huai-chen (Frontiers in Public Health, 2021)
Background: Drug-resistant tuberculosis (DR-TB), especially multidrug-resistant tuberculosis (MDR-TB) is a public health threat. Little is known about estimates of different profiles and rates of DR-TB among children globally. Methods: We did a systematic review and meta-analysis of studies reporting DR-TB among children by searching Embase, PubMed, and Scopus databases up to 1 October 2020. Publications reporting more than 60 children with bacteriological confirmed tuberculosis and phenotypical drug susceptibility testing (DST) results were included. Pooled proportions of MDR-TB and sub-analysis by age subgroups, regions, economical levels were performed. Results: We identified 4367 studies, of which 37 were included. Of 23652 pediatric TB patients, the proportions of DR-TB, MDR-TB, mono-resistant TB, polydrug resistant TB, extensively drug-resistant TB were 13.59% (1964/14453), 3.72% (881/23652), 6.07% (529/8719), 1.61% (119/7361), 0.44% (30/6763), respectively. The pooled proportion of MDR-TB among 23652 children of 37 studies was 3.7% (95% CI, 3.5%–4.0%). Rate of MDR-TB was much lower in high-income countries (1.8%) than that in lower-middle-income countries (6.3%) and upper-middle-income countries (7.3%). More specifically, the rates of MDR-TB were 1.7% in USA, 1.7% in UK, 2.9% in India, 6.0% in South Africa, 9.8% in China, respectively. Conclusions: The burden of DR-TB remains high in children, and there are potential associations between rates of pediatric MDR-TB and national economical levels. More interventions on child TB cases in low-income countries may be urgently needed in future.